Information Sharing Between Authorities Combating Foreign Labour Exploitation in Finland - Terhi Kankaanranta; Saana Rikkilä; Kimmo Kuukasjärvi (Nordic Journal of Studies in Policing)
Well-functioning information sharing is an essential element for successful cooperation between authorities in public administration, e.g., when authorities attempt to combat foreign labour exploitation. This paper contributes toward existing literature by broadening the understanding about factors that need to be acknowledged when developing information sharing practices between authorities. The purpose of this study was to analyse authorities’ perceptions of possibilities and obstacles to share information with a focus on legislation, IT infrastructure and the set of electronic registers. In this case, the authorities were those whose legal duties include supervision of work-related immigration. In addition to a summary of legislation, empirical data was used. An electronic questionnaire was sent to 14 relevant authorities (62 respondents); 12 authorities responded. Knowledge gaps related to legislation and content of information were found to hamper information sharing between authorities. In addition, IT infrastructure capability and the fragmented nature of data registers, the so-called ‘silo effect’, complicates information distribution. To secure efficient and smooth information sharing, authorities need to know their legal possibilities and their duties to share information, but also understand what information is valuable to other authorities. In addition, IT infrastructure capability needs to be developed further. Finally, increasing knowledge about legal aspects is an important topic in education.